2016
DOI: 10.1177/1524839916679104
|View full text |Cite
|
Sign up to set email alerts
|

“What’s Cooking?”: Qualitative Evaluation of a Head Start Parent–Child Pilot Cooking Program

Abstract: Providing access to nutritious foods is crucial for low-income populations, but increasing nutrition-related skills and attitudes such as food preparation, feeding practices, and positive perceptions around healthy foods to establish sustainable behavior change are paramount for the development of healthy lifestyles. This qualitative study was designed to evaluate the What's Cooking pilot program. A total of 15 participants were recruited from two Head Start schools through flyers, text messages, and e-mails. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…For many participants, this opportunity alone was appreciated. The observation that parents and children connected positively in different ways is an important finding itself, which echoes the findings of previous studies on joint cooking classes, namely, that cooking classes for parents and children not only increase knowledge and confidence in cooking but also support family connections and family food environments [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For many participants, this opportunity alone was appreciated. The observation that parents and children connected positively in different ways is an important finding itself, which echoes the findings of previous studies on joint cooking classes, namely, that cooking classes for parents and children not only increase knowledge and confidence in cooking but also support family connections and family food environments [ 26 ].…”
Section: Discussionsupporting
confidence: 81%
“…Further, studies investigating children’s participation in meal preparation at home suggest that the social activity of cooking offers a rich opportunity for positive parent–child bonding [ 25 ]. Nevertheless, limited research exists on joint cooking programs and how these potentially strengthen parent–child relations [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that cooking classes can have positive effects on parents, such as increased self-efficacy for meal preparation (Herbert et al, 2014; Morin et al, 2013). While there is a need for further examination of cooking classes that involve both parents and children, a few studies have examined such classes and reported positive outcomes including improvements in HE-PA behaviors (Anderson et al, 2015; Miller et al, 2017).…”
Section: Implications For Future Researchmentioning
confidence: 99%
“…increasing fruit and vegetables intakes, 20,25 less consumption of takeaway/fast foods and ready meals, and less consumption of convenience foods, discretionary food and drinks. 46 Family meals provide an opportunity to expose children to healthy food, observe others eating through role modelling, and establish routines and behaviours in a familiar social setting.…”
Section: Food Literacy Behavioursmentioning
confidence: 99%
“…There have been several international interventions (USA, Germany and New Zealand) targeting parents of 0-5 years that combine food literacy and positive parenting feeding practices. [20][21][22][23][24][25] These have reported positive impacts on children's dietary intakes 20 and improvements in parenting feeding practices. 22 The duration of these interventions ranged from 6 weeks 24 to 18 months.…”
Section: Introductionmentioning
confidence: 99%